IDEOLOGISASI NILAI DHARMA AGAMA DAN DHARMA NEGARA MELALUI PENDIDIKAN NONFORMAL DI PC KMHDI DENPASAR - Permana, I Dewa Gede Darma (Institut Agama Hindu Negeri Gde Pudja Mataram, 2025)
Radicalism is one of the challenges that needs to be faced by the Indonesian state. Through a pluralistic nation in terms of religion and culture, Indonesia is prone to being infiltrated by individuals who divide the nation. Therefore, a balance in carrying out obligations as citizens and religious believers needs to be sought from an early age. This is what is done by one of the youth organizations called Pimpinan Cabang Kesatuan Mahasiswa Hindu Dharma (PC KMHDI) Denpasar, by ideologizing the value of Dharma Agama and Dharma Negara through non-formal education. On this basis, this research is present with the aim of describing in depth the ideologization of the values of Dharma Agama and Dharma Negara through Nonformal Education in PC KMHDI Denpasar. Based on the topic, three problems were formulated, namely the value of Dharma Agama in the KMHDI perspective, the value of Dharma Negara in the KMHDI perspective, and the ideologization of these two values through Nonfromal Education in KMHDI. Relying on the type of qualitative research that uses a naturalistic approach, this research shows the results and discussion, that: 1) Ideologization of Dharma Agama is based on Vedic values with the aim of realizing Hindu intellectuals who are Moksartham Jagadhita Ya Ca Iti Dharma. 2) The ideologization of Dharma Negara relies on Pancasila to realize the goal of an Independent Indonesia. 3) The ideologization of both values is carried out through Non-formal Education called “Kaderisasi Tahap 1”, which makes an important contribution to religion and the state.